Impact on the intestinal microbiota of early antibiotic treatment in preterm neonates - Zhu, W W (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2018)
Objective: To investigate the impact of early antibiotics treatment on intestinal microbiota in preterm infants. Methods: The cohort study was performed from January 2015 to June 2015 in Neonatal Intensive Care Unit of Peking University Third Hospital. A total of 33 preterm infants were enrolled, among whom 25 were antibiotics-exposure group, and 8 were non-exposure group. Serial stool samples were collected on the first day, 14th and 30th days of life and analyzed by high-throughput sequencing. In exposure group, intestinal microbiota was also analyzed at 8 months to 1 year of age. Categorical variables were analyzed with χ(2) test, and continuous variables were analyzed with t test or non-parametric test. Results:Proteobacteria was the most prominent flora after birth in all cases (exposure group 69.6%, non-exposure group 83.7%) . In exposure group, at the phylum level, Proteobacteria was the dominant bacteria within the first 30 days, followed by Firmicutes after 30 days of life. At the genus level, Escherichia was the most abundant genera within 30 days after birth, while Veillonella became dominant after 8 months to 1 year of life. In non-exposure group, at the phylum level, Proteobacteria was the dominant phylum within the first 30 days. At the genus level, Actinobacteria (37.5%) was the dominant genus after birth, followed by Escherichia within the first month. Intestinal bacterial abundance and diversity were lower in exposure group, which was most significant on 30th day of life (shannon index 2.6 vs.3.4, ACE index 563.9 vs.591.6) . The influence of single antibiotics was less significant than combined treatment (shannon index 2.7 vs.2.5, ACE index 727.3 vs.492.9) . At the genus level, compared to non-exposure group, there were significant decrease of Escherichia (9.3% vs. 54.3%, Z=-2.830, P=0.005), Klebsiella (0.03% vs.12.4%,Z=-2.240, P=0.025), and Clostridium (0.2% vs. 4.8%, Z=-2.979, P=0.003) in exposure group on 14 days of life. Bifidobacterium (0.1% vs.2.0%, Z=-2.349, P=0.019) in cases treated with combined antibiotics was lower than that treated with antibiotic monotherapy on 30 days of life. Conclusions: Early application of combined antibiotics impacts on the intestinal microbiome of preterm infants significantly. The infants who have received antibiotic after birth have lower quantity and diversity of Clostridium, Lactobacillus, Bacteroides and Bifidobacterium